Cheating at the top: Trait dominance explains dishonesty more consistently than social power - Kim, K.-H.; Guinote, A. (Personality and Social Psychology Bulletin, 2022)
Power has long been associated with dishonesty. Here we examined the contributions of personal and structural factors associated with power. Across 5 studies (N = 1,366), we tested the hypothesis that being dominant, more than having power and felt prestige, predicts dishonesty in incentivized tasks, moral disengagement, and breaking of Covid-19 containment rules. Dominance and dishonesty were positively associated (Study 1). Furthermore, dominance contributed to the positive relationship between occupational power and dishonesty in natural settings (Studies 2, 5). Different types of power had inconsistent effects on dishonesty (Studies 3, 4). Prestige was unrelated to dishonesty. Dominant individuals were overrepresented at the top, suggesting that the association between power and dishonesty may derive from self-selection processes, rather than power itself.